Criminal accountability of state owned enterprises in criminal acts of corruption - Akhmad Taufik,; Slamet Suhartono,; Yovita Arie Mangesti,; Erny Herlin Setyorini, (Technium Social Sciences Journal, 2023)
State-Owned Enterprises (BUMN) (hereinafter referred to as BUMN) are one of economic actors that contribute to the development of state finances. SOEs as corporations can run a variety of businesses such as health services, implementation of banking services, industry players, the transportation sector, services in the field of providing goods and services, and so on. In addition to contributing in the form of profits from its business sector, State-Owned Enterprises (BUMN) also contribute in the form of paying taxes to the state. Business fields managed by BUMN are basically profit-oriented, so that all business activities of State-Owned Enterprises (BUMN) are directed towards the goal of achieving profit. The separation of criminal responsibility is very important to explain, bearing in mind that in Article 20 paragraph (2) of the Corruption Crime Law, it is only formulated that: -alone or together". The formulation of the article with the sentence "...acting in a corporation..." shows that corporations are subjects of criminal law. It is this doctrine of the corporation as a legal subject that influences the development of corporate criminal responsibility as the perpetrator of corporate crime at this time.